2017
DOI: 10.4067/s0717-95022017000401363
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Inhibits Chronic Stress-Induced Myocardial Infarction in Rats

Abstract: Ismaeel Bin-Jaliah BIN-JALIAH, I. Quercetin inhibits chronic stress-induced myocardial infarction in rats. Int. J. Morphol., 35(4):1363Morphol., 35(4): -1369Morphol., 35(4): , 2017. SUMMARY:We recently reported that chronic unpredictable stress (CUS) induced left ventricular dysfunction (LVD) in rats, which was inhibited by the cardioprotective agent quercetin. Based on these findings and because majority of patients with myocardial infarction (MI) can develop LVD and heart failure, we sought to produce an ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Doxorubicin was selected as a common chemotherapy drug [ 16 , 17 , 18 , 19 ], and a cumulative dose of 18 mg/kg was used in 6 injections every other day via intraperitoneal injection (IP). Due to the antioxidant role of quercetin [ 20 , 21 , 22 , 23 , 24 ], this herbal substance (purity > 95%) (Sigma, USA) was selected and administered daily by gavage at a dose of 50 mg/kg with a normal saline carrier for 11 days. Rats were randomly divided into seven groups of six members as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Doxorubicin was selected as a common chemotherapy drug [ 16 , 17 , 18 , 19 ], and a cumulative dose of 18 mg/kg was used in 6 injections every other day via intraperitoneal injection (IP). Due to the antioxidant role of quercetin [ 20 , 21 , 22 , 23 , 24 ], this herbal substance (purity > 95%) (Sigma, USA) was selected and administered daily by gavage at a dose of 50 mg/kg with a normal saline carrier for 11 days. Rats were randomly divided into seven groups of six members as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Rats were classified into 5 groups (n = 12/group) in the following order: 1) Control sham-operated group: had a similar sham surgical procure without tying the left anterior descending (LAD) coronary artery and then received an equivalent oral dose of 0.5% carboxymethyl cellulose (CMC) (a vehicle), daily, for the next 30 days; 2) Control + QUR treated group: had similar sham surgery as in group but then received QUR (prepared in 0.5% CMC) (50 mg/kg/orally) for 30 days; 3) MI-induced group: were rats with pre-established MI and received 0.5% CMC as a vehicle for the next 30 days starting 1 h after the induction of MI, and 4) MI + QUR-treated group: were rats with pre-established MI and administered QUR solution, 1 h post-induction of MI (50 mg/kg/orally) and continued for the next 30 days starting. The preparation, dose, and route of administration of this QUR were adopted from previous studies, which demonstrated cardioprotective and anti-fibrotic effects of QUR at this dose ( Zaafan et al, 2013 , Bin-Jaliah, 2017 , Wang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thereby concluded that quercetin has cardio-protective potential and established its mechanism of action against isoproterenol-induced myocardial infarction (MI) in experimental rats. The inhibition of chronic-unpredictable-stress-(CUS)-induced left ventricular dysfunction (LVD) in rats by quercetin in an animal model was studied by Bin-Jaliah [40]. It was hypothesized that quercetin tends to prevent myocardial infarction (MI) induction by CUS.…”
Section: Quercetin As a Cardioprotective Agentmentioning
confidence: 99%
“…Furthermore, the significant inhibition of expression of Bax RNA messages and blocked CUS-induced TNF-α and IL-6 upregulation led to the efficacy of quercetin treatment. Thus, a possible therapeutic role for quercetin in CUS-induced cardiac dysfunction was established by Bin-Jaliah [40]. Quercetin was studied for its effect on myocardial ischemia in patients with stable coronary heart disease (CHD) by Chekalina et al [41].…”
Section: Quercetin As a Cardioprotective Agentmentioning
confidence: 99%